HPLC-MS-MS quantification of short-chain fatty acids actively secreted by probiotic strains - Calvigioni, Marco; Bertolini, Andrea; Codini, Simone; Mazzantini, Diletta; Panattoni, Adelaide; Massimino, Mariacristina; Celandroni, Francesco; Zucchi, Riccardo; Saba, Alessandro; Ghelardi, Emilia (Frontiers in Microbiology, 2023)
Short-chain fatty acids (SCFAs) are the main by-products of microbial fermentations occurring in the human intestine and are directly involved in the host’s physiological balance. As impaired gut concentrations of acetic, propionic, and butyric acids are often associated with systemic disorders, the administration of SCFA-producing microorganisms has been suggested as attractive approach to solve symptoms related to SCFA deficiency. In this research, nine probiotic strains (Bacillus clausii NR, OC, SIN, and T, Bacillus coagulans ATCC 7050, Bifidobacterium breve DSM 16604, Limosilactobacillus reuteri DSM 17938, Lacticaseibacillus rhamnosus ATCC 53103, and Saccharomyces boulardii CNCM I-745) commonly included in commercial formulations were tested for their ability to secrete SCFAs by using an improved protocol in high-performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS-MS). The developed method was highly sensitive and specific, showing excellent limits of detection and quantification of secreted SCFAs. All tested microorganisms were shown to secrete acetic acid, with only B. clausii and S. boulardii additionally able to produce propionic and butyric acids. Quantitative differences in the secretion of SCFAs were also evidenced. The experimental approach described in this study may contribute to the characterization of probiotics as SCFA-producing organisms, a crucial stage toward their application to improve SCFA deficiency.